PKM OLAHAN IKAN TUNA DESA SITIARJO KEC.SUMBERMANJING WETAN KAB.MALANG JAWA TIMUR - Wiyarni Wiyarni; Eko Sudjawoto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Partners in the Community Partnership Program (PKM) are micro entrepreneurs making shredded tuna, smoked fish and tuna crackers in Sitiarjo Village Sumbermanjing Wetan District Malang Regency. The raw material for making partner products, namely tuna fish, is obtained from Sendang Biru Beach, which is the biggest auction place for fish in East Java, about 10 thousand tons of tuna and / or tuna fish per year is caught by fishermen on Sendang Biru Beach. The problem faced by partners is the quality of shredded products and their packaging is low so as to make products prone to damage. In addition, the level of productivity is low due to the use of small capacity cooking utensils, managerial skills and knowledge (work), work ethics, marketing management that is understood by partners is very limited and there is no financial recording.The method used during the implementation of this service is the method of active participation between program implementers and partners in providing raw materials and places during the serviceThe solution to solve the problems faced by partners is to design and reduce oil content, increase the capacity of cooking utensils, vacuum sealers, and trainings (entrepreneurship, marketing and bookkeeping).